THE INFLUENCE OF SIC ON THE OXIDATION RESISTANCE OF HIGH ENTROPY ALLOY COMPOSITE COATING AL70(FE-CR-NI)30-X(SIC)X ON AISI 1018 STEEL (X = 0; 10; 15) - Yehuda Natasurya, Daniel
Low carbon steel is one type of steel material that is widely used because it has several advantages in mechanical properties, formability properties, abundant presence, and relatively lower price compared to other materials. However, the poor oxidation resistance of low carbon steels is one of the main limitations in their use under elevated temperature working conditions. In this study, a coating process to increase the oxidation resistance of low carbon steel was carried out on AISI 1018 low carbon steel substrate using High Entropy Alloy (HEA) composite coating Al70(Fe-Cr-Ni)30-x(SiC)x with different silicon carbide (SiC) value of X or atomic percentage content, namely 0%, 10%, and 15% with sample codes 0 SiC, 10 SiC, and 15 SiC. It was processed using the Mechanical Alloying (MA) method. The oxidation resistance testing of the samples was conducted using isothermal oxidation test and electrochemical impedance spectroscopy. The formed phases, observation of coating layers, and oxidation resistance of the composite coating were studied for the first time and evaluated using X-Ray diffraction (XRD), optical microscope (OM), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). All coating samples can fully cover the substrate, with a coating thickness ranging from 99.186 ?m to 104.131 ?m. The results of isothermal oxidation testing method for 100 hours at a temperature of 800°C show that the weight gain per unit surface area for coating samples with 0, 10, and 15 SiC respectively are 31.00401 mg/cm2, 19.87013 mg/cm2, and 25.48227 mg/cm2. Electrochemical impedance spectroscopy (EIS) testing using 0.1 M Na2SO4 solution indicates that the impedance values for coating samples with 0, 10, and 15 SiC respectively have resistance R1 values of 1.88 x 104 ? cm2, 3.67 x 104 ? cm2, and 2.01 x 104 ? cm2. After undergoing isothermal oxidation testing, the presence of Al2O3 layer and nodules (Fe oxidation) is observed on the entire coating surface. In this case, the 10 SiC sample yields optimal results with improved layer thickness, resulting in smaller nodule size formation. Additionally, this sample also exhibits the lowest weight gain and the highest R1 resistance value.